Donor–Acceptor Metallopolymers Containing Ferrocene for Brain Inspired Memristive Devices. (8th October 2020) - Zhang, Miaocheng; Ma, Chenxi; Du, Dawei; Xiang, Jing; Yao, Suhao; Hu, Ertao; Liu, Shujuan; Tong, Yi; Wong, Wai‐Yeung; Zhao, Qiang
Abstract: To realize brain‐inspired devices and systems, memristor is one of the significant alternatives in breaking through the infrastructure restrictions of present logic and memory devices. Organic materials have become popular to fabricate memristive devices due to their unique properties of low cost, mechanical flexibility, and compatibility with complementary metal‐oxide‐semiconductor technology. Metallopolymer is a new kind of promising organic materials functioning as the resistive‐switching layers of memristive devices due to the unique donor–acceptor type structure, which performs good ability of tuning electron concentration to boost the migration of inner ions. Herein, a new metallopolymer MP1 containing ferrocene and triphenylamine is designed and synthesized, which is utilized as a resistive‐switching layer of memristor with active and inert electrodes of Ag and Pt, respectively. Process flow of devices is fully developed and MP1 is found to act as metal‐ions‐accommodation site with the great potential to boost the formation of conductive filaments in the active region. More interestingly, the conductance of Ag/MP1/Pt memristor can be modulated under various voltage pulses exhibiting distinguished electrical properties. Additionally, synaptic functions are successfully emulated using such MP1‐based memristors. This work will greatly expand the further development of organic memristors for flexible brain‐inspired systems. Abstract : A new metallopolymer MP1 containing ferrocene and triphenylamine is designed and synthesized, which is utilized as the active layer of memristor with electrodes of Ag and Pt. MP1 is found to act as metal‐ions‐accommodation site and has great potential to help the formation of conductive filaments in active region. Additionally, synaptic functions are successfully emulated using MP1 memristor.